#### WannabeNewton

Science Advisor

- 5,774

- 526

We have that [itex]\mathcal{L}_{\psi}\omega _{a} = \mathcal{L}_{\psi}(\epsilon _{abcd}\xi ^{b}\triangledown^{c}\xi ^{d}) = \epsilon _{abcd}\mathcal{L}_{\psi}(\xi ^{b}\triangledown^{c}\xi ^{d}) + \xi ^{b}\triangledown^{c}\xi ^{d}\mathcal{L}_{\psi}\epsilon _{abcd}[/itex]. Starting with the first expression, we have [itex]\mathcal{L}_{\psi}(\xi ^{b}\triangledown^{c}\xi ^{d}) = \triangledown ^{c}\xi ^{d}\mathcal{L}_{\psi}\xi ^{b} + \xi ^{b}\mathcal{L}_{\psi}(\triangledown ^{c}\xi ^{d}) = \xi ^{b}\mathcal{L}_{\psi}(\triangledown ^{c}\xi ^{d}) [/itex] where I have used the fact that [itex][\xi ,\psi ] = 0[/itex].

[itex]\mathcal{L}_{\psi}(\triangledown ^{c}\xi ^{d}) = (\psi ^{e}\triangledown _{e}\triangledown ^{c}\xi ^{d} - \triangledown ^{c}\xi ^{d}\triangledown _{e}\psi ^{c} - \triangledown ^{c}\xi ^{e}\triangledown _{e}\psi ^{d}) [/itex]. We have that [itex]\psi ^{e}\triangledown _{e}\triangledown ^{c}\xi ^{d} = R^{dc}{}_{ef}\psi ^{e}\psi ^{f} = R^{dc}{}_{[ef]}\psi ^{(e}\psi ^{f)} = 0[/itex] therefore [itex]\mathcal{L}_{\psi}(\triangledown ^{c}\xi ^{d}) = - \triangledown ^{c}\xi ^{d}\triangledown _{e}\psi ^{c} - \triangledown ^{c}\xi ^{e}\triangledown _{e}\psi ^{d} = \triangledown ^{d}\xi ^{e}\triangledown _{e}\psi ^{c} - \triangledown ^{d}\psi ^{e}\triangledown _{e}\xi ^{c}[/itex]. Now, [itex]\mathcal{L}_{\psi}\xi ^{c} = 0 \Rightarrow \xi ^{e}\triangledown _{e}\psi ^{c} = \psi^{e}\triangledown _{e}\xi ^{c}\Rightarrow \triangledown ^{d}( \xi ^{e}\triangledown _{e}\psi ^{c}) = \triangledown ^{d}(\psi^{e}\triangledown _{e}\xi ^{c})[/itex] so we can conclude that [itex]\triangledown ^{d}\xi ^{e}\triangledown _{e}\psi ^{c} - \triangledown ^{d}\psi ^{e}\triangledown _{e}\xi ^{c} = \psi ^{e}\triangledown ^{d}\triangledown _{e}\xi ^{c} - \xi ^{e}\triangledown ^{d}\triangledown _{e}\psi ^{c} = \psi ^{e}\xi ^{f}(R^{d}{}_{ef}{}^{c} + R^{d}{}_{f}{}^{c}{}_{e}) = -\psi ^{e}\xi ^{f}R^{dc}{}_{ef} = 0[/itex], where I have used the Bianchi identity, thus [itex]\mathcal{L}_{\psi}(\triangledown ^{c}\xi ^{d}) = 0[/itex].

Now for the second expression, first I'll prove the following claim: let [itex]\mathbf{T}[/itex] be a rank 2 tensor then [itex]\sum_{k}\epsilon _{a_1...a_{k-1}ja_{k+1}...a_{n}}T^{j}_{a_k} = \epsilon _{a_1...a_n}T^{j}_j[/itex]. To do this, first let [itex]k\in \left \{ 1,...,n \right \}[/itex] be fixed but arbitrary. Note that [itex]\forall j\neq a_k[/itex], [itex]\epsilon _{a_1...a_{k-1}ja_{k+1}...a_{n}}T^{j}_{a_k} = 0[/itex] because we would have a repeated index and by definition of the levi - civita symbol, a component with two or more repeated indices vanishes. Therefore, [itex]\epsilon _{a_1...a_{k-1}ja_{k+1}...a_{n}}T^{j}_{a_k} = \epsilon _{a_1...a_{k-1}a_ka_{k+1}...a_{n}}T^{a_k}_{a_k} =\epsilon _{a_1...a_{n}}T^{a_k}_{a_k} [/itex]. Because [itex]k[/itex] was arbitrary, [itex]\sum_{k}\epsilon _{a_1...a_{k-1}ja_{k+1}...a_{n}}T^{j}_{a_k} = \epsilon _{a_1...a_n}\sum_{k}T^{a_k}_{a_k} =\epsilon _{a_1...a_n}T^{j}_j [/itex]. Using this, [itex]\mathcal{L}_{\psi}\epsilon _{abcd} = \psi ^{e}\triangledown _{e}\epsilon _{abcd} + \sum_{k}\epsilon _{a..e..d}\triangledown _{a_k}\psi ^{e} = \epsilon _{abcd}\triangledown _{e}\psi ^{e} = 0[/itex] where the facts that the covariant derivative of the levi - civita symbol vanishes and that killing fields are divergence free have been used. This finally gives us [itex]\mathcal{L}_{\psi}\omega _{a} = 0[/itex].

I really, really appreciate any and all help on finding mistakes in the solution and/or flaws in any arguments. Sorry for the long winded post. Cheers!